Analytical techniques for studying the physical properties of lipid emulsions - Herrera, Maria Lidia (SpringerBriefs in food, health, and nutrition, 2012)
Examples of emulsion-based foods include ice cream, yoghurt, and mayonnaise. Several techniques are used to study the physical behavior and structure of emulsions. Among the oldest methods used is visual observation and small deformation rheometry. This book reviews old and new methods to study emulsion stability and structure